Directions in recursion of tropical nights at the Diwaniya and Al- Hayy stations - Salim Hashim Al-Jabiri , Saja; Ghlis Nahi Al-Saeedy , Prof. Dr.Ali (Basra studies journal, 2022)
Climate change poses serious environmental threats to agriculture, hydrometeorology, human health, etc. The study area has undergone climatic changes in various elements. Thermal radicalization and increasing frequency may be one of the climatic characteristics of the change. The current study explores changes in the frequency of tropical nights using the daily temperature data for the 1958-2019 period. The study shows that there is a general direction of increasing the frequency of tropical nights, especially in the second period. (1989-2019) secondary evidence (25.1-29.9) and (30) While the context is unique (20,1-25) AD by a decrease in its frequency in the second period